Hold back the dark [compact disc, unabridged] - Hooper, Kay (A Bishop/SCU novel, 2018)
Trapped in a nightmare they can't escape, the residents of Prosperity are killing one another, waking up with no memory of the monstrous acts they've committed, or the reasons why. Chief Deputy Katie Cole knows that whatever evil is afoot is beyond her expertise, and beyond the understanding of Sheriff Jackson Archer. They need help.